2011
DOI: 10.1126/science.1204636
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Isotopic Composition of the Sun Inferred from Captured Solar Wind

Abstract: All planetary materials sampled thus far vary in their relative abundance of the major isotope of oxygen, (16)O, such that it has not been possible to define a primordial solar system composition. We measured the oxygen isotopic composition of solar wind captured and returned to Earth by NASA's Genesis mission. Our results demonstrate that the Sun is highly enriched in (16)O relative to the Earth, Moon, Mars, and bulk meteorites. Because the solar photosphere preserves the average isotopic composition of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
304
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(329 citation statements)
references
References 53 publications
23
304
2
Order By: Relevance
“…[5][6][7][8][9] Observations have shown that the rare heavy isotopes for both O and N are enriched on the Earth compared with the sun and solar nebula. 10,11 A similar behavior is expected in the interstellar medium as well as around young stars. The 15 N isotope is more enriched (about 40%) on the Earth than 17 O (about 6%) but the reason why it is so is not yet understood.…”
Section: Introductionmentioning
confidence: 49%
“…[5][6][7][8][9] Observations have shown that the rare heavy isotopes for both O and N are enriched on the Earth compared with the sun and solar nebula. 10,11 A similar behavior is expected in the interstellar medium as well as around young stars. The 15 N isotope is more enriched (about 40%) on the Earth than 17 O (about 6%) but the reason why it is so is not yet understood.…”
Section: Introductionmentioning
confidence: 49%
“…A galactic origin for the initial abundance of 182 Hf recorded by the FUN and canonical CAIs requires ∼18 Ma of free decay between last nucleosynthetic event that produced the heavy (31), the oxygen-isotope compositions of anorthite, spinel, hibonite, and most Al,Ti-diopside grains in STP-1 plot along a massdependent fractionation line defining an initial Δ 17 O value of ∼ −24‰, that is, similar to the oxygen-isotope composition of canonical CAIs and that of the Sun (31,32). Oxygen-isotope compositions of melilite and some of the Al,Ti-diopside grains plot along a line with a slope of ∼1, suggesting subsequent isotope exchange with a 16 O-depleted gaseous reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed thermo-chemical models confirm that this can have a significant impact on the C 18 O emission from low-mass disks though not for such massive disks as HD 163296 (Miotello et al 2014). Future observations of T Tauri disks can examine this important effect and assess whether it may explain the variation of oxygen isotopes in the Solar System (McKeegan et al 2011). …”
Section: As a Rare Isotopologue Cmentioning
confidence: 99%